Application of Project-Based Learning in Classrooms: An Innovative Pedagogy for Sustainable Education - Adhikari, Gopi Raj (Academia Journal of Humanities & Social Sciences, 2024)
In this modern age, the learners want practicable knowledge to adapt to the fast pace of technological modernization. This research has dealt the very concept of application of project based learning (PBL) approach in teaching learning activities. It develops their inherent ability enhancing sustainable education exploring their ability, and strengthening confidence for their all-round development. The qualitative research has been designed with the questionnaire accessing 50 respondents. The core area of the research is Janaprakash Secondary School of Pokhara-29, Gandaki Province, Nepal. The primary data have been collected and literature reviews have been supportive for the research. Similarly, 15 different questions have been developed for the research. For the validity 10 secondary level experienced teachers have been asked to respond to the questionnaire. Professionally teachers and students, and demographically males and females of 15 to 55 years old respondents have been selected for responses. The results show that the PBL approach is applicable to enhance the sustainable development of the new era through education. The study concludes that an application of PBL in teaching learning activities enhances the competence of the learners.